PENGARUH UKURAN PERUSAHAAN, LEVERAGE, DAN PROFITABILITAS TERHADAP INCOME SMOOTHING PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2014-2018 - Tri Setyaningsih; Titiek Puji Astuti; Yunus Harjito (ITB AAS INDONESIA Surakarta, 2021)
This Study aims to examine the effect of firm size, leverage and profitability on income smoothing of the manufacturers registered at the Indonesia’s Stock Exchange in 2014-2018. Type of research in this study is quantitative research. The data used be in the form of secondary data taken based on the company’s financial statements in manufacturing companies listed on Indonesia Stock Exchange in 2014-2018. The sampling technique of this study uses purposive sampling method. The analysis method of this research uses a regression analysis with Eviews 9 Version. Based on the result of analysis data in this research showes that the firm size have a positive effect on income smoothing while the leverage and profitability does not effect on income smoothing in manufacturing companies listed on Indonesia Stock Exchange in 2014-2018. Keywords: Firm Size, Leverage, Profitability, Income Smoothing